CARCINOMA CHEEK: REGIONAL PATTERN AND MANAGEMENT - Musani, Muhammad Ayub; Jawed, Itrat; Marfani, Saleem; Khambaty, Yousuf; Jalisi, M.; Khan, Shahbaz Ali (Journal of Ayub Medical College Abbottabad, 2009)
Background: Oral cancer varies globally and regionally, and is closely linked with geographical, social, economical, biological, ethnic, dietary and environmental factors. In western countries it accounts for about 2-5% while in the south-east Asia for about 40% of all cancers. In Pakistan it is second commonest tumour after bronchogenic carcinoma in males and breast carcinoma in females. The objectives of this study were to find out the pattern of carcinoma cheek in our region, its etiological associations, management and prognosis. This study was conducted in the Otolaryngology and Head and Neck Surgery Department of Civil Hospital, Karachi from April 1995 to December 1998. It was prospective study. Methods: Forty-five cases of primary carcinoma cheek were diagnosed and investigations including OPG and CT scan were carried out along with other required investigations to evaluate the extension of tumour, bony erosion and metastasis. TNM staging was done. All patients were treated surgically, sent for post-operative radiotherapy or chemoradiation and followed up for 3 years. Result: Among 45 cases of oral cancer, 28 were females and 17 were males. Common presenting symptom was growth or ulcer. It was more common in 41-50 years of age. Squamous cell carcinoma (SCC) was found in 95.5% of the cases. Most of the patients 31 (68%) were in T4 stage. Surgical excision was done in all cases with reconstructuion in 23 cases and neck dissection in 39 cases. In the follow up for 3 years, 30 patient remained disease free. Conclusion: Carcinoma cheek is a common entity in our region and now it is seen in relatively younger patients. Oral cancer is a self preventable disease. What is required is to develop awareness of oral hygiene and discourage the habit of social carcinogens use. Early diagnosis and treatment offers better chance of cure whereas advance disease has a poor prognosis. Keywords: Oral cavity squamous cell carcinoma (OSCC), supraomohyoid neck dissection.